Colossians, Philemon - Watt, Jonathan M. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
This exegetical, linguistic commentary on the New Testament epistles of Colossians and Philemon brings discourse analysis into connection with exegesis of the Greek text. It aims to connect theoretical approaches to the ancient Greek with current interests such as biblical interpretation, appreciation of the original circumstances behind its composition, and relevance of these early epistles to modern readers